Clinical response to microminerals with vitamin E supplementation in anoestrus Deoni cows - MARKANDEYA, N M; BHIKANE, A U; BHARKAD, G P (The Indian Journal of Animal Reproduction, 2023)
Micromineral with Vitamin E supplementation for a pericxl of 15 days resulted into initiation of follicular development and 75 per cent animals showed ovulatory oestrus within 6 to 9 days post treatment in postpartum anoestrus Deooi cows. All the responded animals conceived with 1. 9 _services per conception.